Estimation of viscoelastic material parameters of polymers using Lamb waves - Johannesmann, Sarah; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Inverses Verfahren zur Bestimmung viskoelastischer Materialparameter - Johannesmann, Sarah

Lydia Böttger (Universität Paderborn) rezensiert: Michalak, Magdalena; Döll, Marion (Hrsg.) (2021): Lehrwerke und Lehrmaterialien im Kontext des Deutschen als Zweitsprache und der sprachlichen Bildung. [Deutsch als Zweitsprache Positionen, Perspektiven, Potenziale, Bd. 2]. Münster, New York: Waxmann, 164 Seiten. ISBN 978-3-8309-4105-7. - Böttger, Lydia (www.daz-portal.de)

Performing Utopia? The Contestation of Dystopian Space in Cecelia Ahern's Flawed-Series - Schneider, Julia Christina (Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre)

Investigation into Target Speaking Rate Adaptation for Voice Conversion - Kuhlmann, Michael; Seebauer, Fritz; Ebbers, Janek; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2022)

Schorsch Kamerun: „Extra Vages machen wir aus tiefer Überzeugung“. - Jacke, Christoph (Kaput. Magazin für Insolvenz & Pop.)

Forward & Rewind: Retromania in Music Documentary. - Jacke, Christoph; Reynolds, Simon (Jugend, Musik und Film.)

Ein kommentierter Tagungsbericht zur 4. Werkstatt Unterrichtsfach Pädagogik Ostwestfalen-Lippe (WUPO) - Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

The Greatest Advantage of Polytheism: Monotheism and Normalization through Truth - Corall, Niklas (Nietzsche's Gods)

What kind of leader am I? An exploration of professionals' leader identity construal - Rehbock, Stephanie K.; Hubner-Benz, Sylvia; Knipfer, Kristin; Peus, Claudia V. (Applied Psychology)
Although the leadership literature has emphasized the importance of leader identity for leader behaviors and leader effectiveness, little is known about whether and how professionals, who are experts in their field and hold a formal leader role, construe a leader identity. To expand our understanding of leader identity construal, we explored how professors in German research universities interpreted their formal leader role and whether and how they saw themselves as leaders. Based on findings from an inductive interview study, we contribute to the literature in three ways: First, our findings imply that patterns of professional identity and leader identity dimensions likely predict when a leader role is rejected , accommodated , incorporated , or emphasized . Second, we explain why professionals with a formal leader role see themselves primarily as specialists , mentors , managers , or shapers . Third, we extend previous notions of the leader identity concept by elaborating on its dimensions. Our findings have practical implications on an individual and organizational level, and may help design more effective leadership development programs.
Keywords: Applied Psychology; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Professionalisierung von Lehramtsstudierenden für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft - Dehn, Freya; Meyer, Anja; Niederhaus, Constanze; Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Aufgrund der heterogenen Schülerschaft im Berufsfeld Ernährung und Hauswirtschaft müssen Studierende für sprachbildenden Fachunterricht professionalisiert werden. Aufbauend auf einer theoretischen Fundierung werden konkrete Umsetzungsbeispiele anhand von drei exemplarischen Online-Modulen für den Ausbildungsberuf Hotelfachfrau/-mann vorgestellt.

Prospective Teachers‘ Competence of Fostering Students’ Understanding in Script Writing Task - Dröse, Jennifer; Wessel, Lena (Proceedings of the 45th Conference of the International Group for the Psychology of Mathematics Education. PME)

Effective vocabulary learning apps: what should they look like? An evaluation with a particular view to German language acquisition - Lentfort, Theresa; Künzl-Snodgrass, Annemarie; de Vincent-Humphreys, Maren (Ab Initio Language Teaching in British Higher Education. The Case of German)

Mental Rotation of Tactic Board Instructions in Basketball: Domain-Specific Expertise Improves On-Court Performance - Krause, Daniel; Weigelt, Matthias (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

GDSU-Journal

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Gemeinsam mehrgleisig an einem Strang. Begleitforschung in InnoVET als Grundlage für nachhaltige Translationsprozesse bei Programmdurchführungen - Ertl, Hubert; Peitz, Nina-Madeleine (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Informed vs. Blind Beamforming in Ad-Hoc Acoustic Sensor Networks for Meeting Transcription - Gburrek, Tobias; Schmalenstroeer, Joerg; Heitkaemper, Jens; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))

Jeanne d’Arc in Bildern vom 15. Jahrhundert bis zur Gegenwart - Moritz, Tilman (Katechetische Blätter)